Sustaining change in schools : how to overcome differences and focus on quality - Johnson, Daniel P. (Alexandria, VA : Association for Supervision and Curriculum Development, 2005)
Explains how partnerships can be created between schools and communities that are beneficial to both students, teachers, and community leaders.
Includes bibliographical references (p. 173-176) and index.
Reference and Research Book News.
Professional
Keywords: Educational leadership -- United States; School management and organization -- United States; Typology (Psychology); Leadership; Schools -- Administration -- United States; Typology (Psychology)